Penentuan Alternatif Keunggulan Kompetitif Ekonomi Kreatif di Kabupaten Aceh Barat: Studi Kasus di Desa Mugo Rayeuk Kecamatan Panton Reu Kabupaten Aceh Barat Provinsi - Alisman, Alisman; Muzakkir, Muzakkir (Jurnal EMT KITA, 2025)
This research was conducted to identify and determine appropriate and rapid alternative strategies for increasing the competitiveness of creative economy products in Mugo Rayeuk Village, developed by the community in support of government programs for creative economy development. This research was conducted using a field study using qualitative research methods. The analysis used a SWOT analysis, which demonstrates the performance of creative industry businesses by determining a combination of internal and external factors. The SWOT analysis, in which both internal and external factors yielded positive results, placed Mugo Rayeuk Village’s creative economy in Quadrant I (Aggressive Quadrant) on the SWOT diagram, a highly favorable situation. Mugo Rayeuk Village possesses both opportunities and strengths, enabling it to capitalize on these opportunities. The strategy that should be implemented in this situation is to support an aggressive growth policy (growth-oriented strategy). A recommended strategy for determining Mugo Rayeuk Village’s competitive advantage, based on the SWOT analysis, can be implemented. With this strategy, Mugo Rayeuk Village can build a competitive advantage based on a combination of historical tourism, agrotourism, culture, and creative products that are competitive at the international level.